2016
DOI: 10.1002/eji.201646581
|View full text |Cite
|
Sign up to set email alerts
|

MAIT be different–persisting dysfunction after DAA‐mediated clearance of chronic hepatitis C virus infection

Abstract: MAIT cells are an abundant innate-like T-cell subset that is defined by the invariant T-cell receptor (iTCR) V-alpha chain Vα7.2-Jα33. Little is currently known about their frequency and function in chronic hepatitis C virus (HCV) infection and their fate after therapy-mediated HCV elimination by direct acting antivirals (DAA). In this issue of theMAIT cells are an abundant innate-like T-cell subset that is defined by the invariant T-cell receptor (iTCR) V-alpha chain Vα7.2-Jα33 [9,10]. Human MAIT cells compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Therefore, since RASs detected by deep sequencing analysis were comparable between responder and treatment-failing patients (60% vs 66.7%), and only 13.3% of additional patients would have failed treatment in the group of patients failing DAAs, systematic deep sequencing analysis is currently not recommended 21 . The role of natural resistance is still controversial due to the high SVR rates, and to date it is relevant only for selected NS3-NS5A inhibitors 28 – 30 , in selected HCV genotypes and clinical settings. Deep analysis on the incidence of RASs at the baseline performed in a larger group of SVR showed that direct sequencing with 15% cut off was able to detect most clinically relevant baseline RASs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, since RASs detected by deep sequencing analysis were comparable between responder and treatment-failing patients (60% vs 66.7%), and only 13.3% of additional patients would have failed treatment in the group of patients failing DAAs, systematic deep sequencing analysis is currently not recommended 21 . The role of natural resistance is still controversial due to the high SVR rates, and to date it is relevant only for selected NS3-NS5A inhibitors 28 – 30 , in selected HCV genotypes and clinical settings. Deep analysis on the incidence of RASs at the baseline performed in a larger group of SVR showed that direct sequencing with 15% cut off was able to detect most clinically relevant baseline RASs 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has become clear that viral infection can modulate both circulating MAIT cell number and function (Barathan et al, 2016;Cosgrove et al, 2013;Eberhard et al, 2014;Fernandez et al, 2015;Hengst et al, 2016;Hofmann and Thimme, 2016;Paquin-Proulx et al, 2017;Vinton et al, 2016), and MAIT cells can be activated by viral infection; however, this is driven in an MR1independent fashion by cytokines, including interleukin-12 (IL-12) and IL-18 Paquin-Proulx et al, 2018;van Wilgenburg et al, 2016). There have been no reports of a link between viral infection and modulation of MR1.…”
Section: Introductionmentioning
confidence: 99%
“…Strunz et al reported a reduced NK cell surface receptor repertoire in HCV infected individuals which persisted well beyond curative treatment [102]. Similar further results were found in mucosal associated invariant T cells, where both reduced numbers and functionality were observed even after successful DAA treatment [113]. Finally, Treg cell numbers remain increased following DAA treatment further limiting the overall functionality of the immune response [114].…”
Section: Hepatocyte Responsementioning
confidence: 77%